Physical-chemical analysis and microbiological quality of in natura buriti (Mauritia flexuosa L.) pulp commercialized in fairs in Manaus-Amazonas (Research, Society and Development, 2021)
The in natura pulp of the buriti tree (Mauritia flexuosa L.) is widely consumed in the northern and northeastern states of Brazil. However, there are few studies related to the quality control of these food products. The objective of this study was to evaluate the physical-chemical properties and microbiological quality of buriti pulp commercialized in Manaus-Amazonas. The samples were collected in fairs in the northern (ZN), southern (ZS), eastern (ZL), western (ZO), central-western (ZCO) and central-southern (ZCS) areas of the city. The pulps were evaluated for pH, ash, titellable acidity expressed in citric acid, total soluble solids expressed in ºBrix and ratio. To determine the microbiological quality, coliforms at 45 °C, Escherichia coli, Salmonella sp. and molds and yeasts were detected. The pH ranged from 3.26 to 3.03 and sample ZL2 presented significant amounts of ash (3.0%). Expressive values of total soluble solids (°Brix) were determined in samples ZCS1 (4.68) and ZL2 (4.64). The average acidity expressed in citric acid and the ratio were 0.36 g.100-1 and 9.10, respectively. The pulps presented high mold and yeast contamination, with significant count (9 x 103 CFU/g) determined in sample ZS1. The growth of coliforms at 45 °C,E. coli and Salmonella sp. was not observed. The results obtained in this study indicate the need for improvements in the quality control of fresh fruit pulps sold at fairs in the capital of Amazonas.